Effects of metabolic energy intervention on lipid content and liver transcriptome in finisher yellow-feathered chickens. Issue 1 (31st December 2022) - Cui, Xiaoyan; Abouelezz, Khaled; Jiang, Zongyong; Gou, Zhongyong; Wang, Yibing; Jiang, Shouqun
Abstract: High-energy diets improve growth rates and shorten the growth period while resulting in excessive fat deposition in the liver of birds. The effect of different energy diets on lipid content and liver transcriptome in finisher Huxu chickens was examined here. A total of 200 90-d-old Huxu chickens with an average BW of 1.08 kg were randomly divided into two dietary treatments. The birds were fed diets either containing 12.06 MJ ME/kg (low metabolic energy, LME) or 13.31 MJ ME/kg (high metabolic energy, HME) for 45 days. Chickens fed the HME diet had significantly higher total triglyceride and total cholesterol concentrations in both plasma and liver than did those fed the LME diet. Transcriptomic profiling showed 480 known differentially expressed genes (DEG), with 180 down-regulated and 300 up-regulated chickens from the HME diet compared with the LME diet. Notably, these genes were mostly enriched in lipid metabolism including the PPAR signalling pathway, fatty acid elongation, and glycerophospholipid metabolism. The relative mRNA expression level of 14 lipid metabolism-related genes, included 13 up-regulated ( MBOAT2, PLA2G2E, AGPAT2, AGPAT3, PCYT2, PEMT, ELOVL2, HADHA, ACOT1L, FABP3, FABP1, PLIN1, RXRG ) and one down-regulated ( LCAT ) gene. In conclusion, the present findings indicate that a high-energy diet likely regulates gene expression of the 14 lipid metabolism-related genes through the PPAR signalling pathway, fatty acid elongation, and glycerophospholipid metabolism resulting in excessive fat accumulation in the liver of Huxu chickens. These results provide a better understanding of the biological mechanisms by which the increased dietary energy induces fat accumulation in the liver. Highlights: A high-energy diet without change in protein level induced excessive fat accumulation in the Huxu chickens. Chickens fed the high-energy diet had induced higher total triglyceride and total cholesterol concentrations in both plasma and liver. This study showed a comprehensive profile of hepatic gene expression in chickens with fatty liver induced by high energy.